2012
DOI: 10.1002/cjg2.1709
|View full text |Cite
|
Sign up to set email alerts
|

The Variation of Waveform and Analysis of Composition for the Geoelectrical Field before Moderate and Strong Earthquakes in Qinghai‐Tibetan Plateau Regions

Abstract: Site‐selective phenomenon exists in the normal waveforms of the geoelectrical fields of Qinghai‐Tibetan Plateau and its adjacent areas: rock structure of the sites, cracks and fissure water, tectonic activity and other factors affect the normal waveforms of the geoelectrical field; a large lake will contribute to the occurrence of TGF‐A waveforms nearby, TGF‐B waveforms will mostly occur in the areas where there are thick Quaternary sediments, and high water content and good water permeability of rocks, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 7 publications
(26 reference statements)
0
21
0
Order By: Relevance
“…For example, on the Qinghai-Tibet plateau, where tectonic activities are intense, various forms of short-impending anomalies could always be detected at more than ten remote E SP or E T stations before and after major earthquakes in recent years. The occurrence time of these anomalies exhibited quasi-synchronization (Tan et al 2010(Tan et al , 2012. In recent years, studies have shown that morphological differences and time quasi-synchronization were also present in the regional trend anomalies of E SP and DE SP (Tan et al 2014), as shown in Fig.…”
Section: Characteristics Of Trend Variation In the Spontaneous Field mentioning
confidence: 81%
See 3 more Smart Citations
“…For example, on the Qinghai-Tibet plateau, where tectonic activities are intense, various forms of short-impending anomalies could always be detected at more than ten remote E SP or E T stations before and after major earthquakes in recent years. The occurrence time of these anomalies exhibited quasi-synchronization (Tan et al 2010(Tan et al , 2012. In recent years, studies have shown that morphological differences and time quasi-synchronization were also present in the regional trend anomalies of E SP and DE SP (Tan et al 2014), as shown in Fig.…”
Section: Characteristics Of Trend Variation In the Spontaneous Field mentioning
confidence: 81%
“…Figure 2e shows that during 2008-2009, the EW and NE long polar distances at Yanyuan station exhibited distinctive diurnal waveforms. E SP , E T , and the adjacent Lugu lake station exhibited quasi-synchronization (Tan et al 2010(Tan et al , 2011(Tan et al , 2012(Tan et al , 2014. However, the day correlation coefficients of long and short distances data in all directions were lower than 0.3.…”
Section: Characteristics Of Trend Variation In the Spontaneous Field mentioning
confidence: 84%
See 2 more Smart Citations
“…Zhao and Lu (2003) pointed out that there existed a correlation between the diurnal variation of apparent resistivity and solid tides; Huang et al (2005; believed that when extracting relatively weak seismic electromagnetic signals from the complex electromagnetic environment, it was necessary to explore a physical analysis method combining math, signal processing and seismic electromagnetic physical process; in the years between 2006, Huang and Liu (2006, Zhang et al (2007) analyzed the spectral characteristics of the solid tidal phenomena of geoelectric field and the variations before earthquakes. Based on the research results on space Sq current by Xu (1992) and Zhao et al (2008), and those on solid tidal waves of geoelectric field by Huang et al (2010a), Tan et al (2010) classified the tidal wave of geoelectric field into two categories of TGF-A and TGF-B, he explored the preliminary principles of physical resolution for spontaneous field and telluric field (Tan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%